2017
DOI: 10.1002/app.46119
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of a water‐soluble, rubber seed oil–based sulfonate and its tribological properties as a water‐based lubricant additive

Abstract: A novel, water-based oleic acid (OA)/2-acryloylamino-2-methyl-1-propanesulfonic acid (AMPS) copolymer was successfully synthesized as a water-based lubricant additive. The OA-AMPS copolymer was characterized by Fourier transform infrared and proton NMR spectroscopies and then used as a lubricant additive in water. The lubrication properties of water-miscible cutting fluids with the OA-AMPS copolymer additive were investigated using a four-ball friction tester. The surface of the wear scars was explored using s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 22 publications
0
8
0
Order By: Relevance
“…For the FLA A additive, the absorption peak at 3446 cm -1 that corresponds to -NH 2 , the absorption peaks at 2929 cm -1 and 2873 cm -1 that correspond to -CH 3 , and the absorption peaks at 1181 cm -1 , 1043 cm -1 , and 632 cm -1 that correspond to -SO 3 - [31] were clearly observed, which represented the AMPS-Na unit that existed on the FLA A polymer chain. Besides, the absorption peaks at 1455 cm -1 corresponded to -CH 2 .…”
Section: Physical and Chemical Properties Of Used Materialsmentioning
confidence: 96%
See 1 more Smart Citation
“…For the FLA A additive, the absorption peak at 3446 cm -1 that corresponds to -NH 2 , the absorption peaks at 2929 cm -1 and 2873 cm -1 that correspond to -CH 3 , and the absorption peaks at 1181 cm -1 , 1043 cm -1 , and 632 cm -1 that correspond to -SO 3 - [31] were clearly observed, which represented the AMPS-Na unit that existed on the FLA A polymer chain. Besides, the absorption peaks at 1455 cm -1 corresponded to -CH 2 .…”
Section: Physical and Chemical Properties Of Used Materialsmentioning
confidence: 96%
“…So, on FLA A, -SO 3 was the main chelating part to Ca 2+ or other high-valence-state metal ions within cementbased materials. For the SXY-2 dispersant, the absorption peak at 3446 cm -1 corresponded to -OH, the absorption peak at 2931 cm -1 corresponded to -C-H, the absorption peak at 1647 cm -1 corresponded to -C=O, and the absorption peak at 1182 cm -1 ,1043 cm -1 , and 617 cm -1 corresponded to -SO 3 - [31], which showed that the dispersant was one type of acetone-formaldehyde-sulfonate-based dispersant [5].…”
Section: Physical and Chemical Properties Of Used Materialsmentioning
confidence: 98%
“…Furthermore, the additive was also able to improve the nonseizure load (P B value) of the water. At concentrations of 0.5%, the P B value reached 431 N, which was three times greater than the water-based lubricant without the additive, and such conditions offered a coefficient of friction of 0.085 and a wear scar diameter of 0.78 mm [60]. Rubber seed oil-based sulfonate is becoming a great candidate for additive implementation within WBLs, allowing the lubricant to maintain environmentally friendly attributes and increasing its capabilities for extreme applications.…”
Section: Other Water-based Lubricant Additivesmentioning
confidence: 99%
“…Additives within a water-based lubricant are often used as a surface-active molecule that reduces friction, wear, and corrosion. Some examples of solid nanoparticle additives are graphene, copper, titanium-di-oxide, and many others [9,12,[57][58][59][60].…”
Section: Water-based Lubricants With Solid Nanoparticlesmentioning
confidence: 99%
“…Therefore, there is an urgent need for an alternative environmentally friendly and low-polluting lubricant. Water-based lubricants are a valid candidate for liquid lubricants because of their low cost, high fire resistance, good storage stability, and excellent biocompatibility [10][11][12].…”
Section: Introductionmentioning
confidence: 99%